Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Sub Sektor Tekstil Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia - Saputra, Romi; EDT, Risa Wahyuni; Fathiah, Fathiah (Universitas Sumatera Barat, 2022)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) on Return on Assets (ROA) in textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study uses an explanatory research approach, namely hypothesis testing research. The population in this study were all manufacturing companies in the Textile and Garment Sub-sector which were listed on the Indonesian Stock Exchange from 2017 to 2021, with a total of 22 companies. The sample used the Purposive Sampling method which aims to obtain a sample according to predetermined criteria with a final sample of 17 companies. The data collection technique is carried out by taking the annual report data (Annual Report) of manufacturing companies in the Textile and Garment Sub-sector which are published on the Indonesia Stock Exchange (IDX), especially in 2017 to 2021, which can be obtained from www.idx.co.id or the website each company, while the data analysis technique uses descriptive statistical analysis, classical assumptions (normality test, linearity test and homogeneity test), simple regression analysis, and hypothesis testing (t test and coefficient of determination). The results showed that the Corporate Social Responsibility variable had an effect on financial performance with a tcount = 5.727 with a significance value of 0.000 <0.05. The coefficient of determination or R Square (R2) is 0.283. To see how big the relationship between Corporate Social Responsibility and financial performance. So the relationship between Corporate Social Responsibility and financial performance is 28.3%. The remaining 100% - 28.3% = 71.7% is influenced by other variables that have not been included in this study.